1975
DOI: 10.1679/aohc1950.37.395
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structure of Taste Buds in the Rat

Abstract: Summary.The taste buds of rat circumvallate papillae contain three distinct types of cells. The type I (dark) cell is characterized by the presence of dense round granules, which are precursor to the dense substance of the taste pore. The granules are discharged into the pore by exocytosis.The type II (light) cell is filled with numerous vesicles and smooth-surfaced endoplasmic reticulum. The type III cell contains in its basal cytoplasm characteristic dark-cored vesicles and masses of clear vesicles, and make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
89
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 148 publications
(102 citation statements)
references
References 35 publications
11
89
2
Order By: Relevance
“…These two kinds of structures were more frequent in the basal extended parts of the cells which were the sites of contact with nerve endings similar in appearance to those seen in the light cells. The occasional occurrence of dark vesicles in the cytoplasm of receptor cells, observed also in the sheep (Tichy 1992b), was in contrast with the data of some authors (Takeda and Hoshino 1975;Takeda 1977) who found clusters or aggregations of these structures in the close vicinity of the area where a nerve ending contacts with the cell. A likely explanation is that the amount of dark vesicles increases with their involvement in transferring stimuli from the cell to a sensory fibre.…”
contrasting
confidence: 99%
See 4 more Smart Citations
“…These two kinds of structures were more frequent in the basal extended parts of the cells which were the sites of contact with nerve endings similar in appearance to those seen in the light cells. The occasional occurrence of dark vesicles in the cytoplasm of receptor cells, observed also in the sheep (Tichy 1992b), was in contrast with the data of some authors (Takeda and Hoshino 1975;Takeda 1977) who found clusters or aggregations of these structures in the close vicinity of the area where a nerve ending contacts with the cell. A likely explanation is that the amount of dark vesicles increases with their involvement in transferring stimuli from the cell to a sensory fibre.…”
contrasting
confidence: 99%
“…The ultrastructure of taste buds on the porcine circumvallate papilla, particularly in the areas of the taste pore and below it, was very similar to that described by Takeda and Hoshino (1975) on fungiform papillae or on in the buds the exposed regions of foliate papillae. The deep and relatively narrow taste pore, small amounts of dark granules in the cytoplasm of type I cells, infrequent and small areas of dark matter in the pore and the fact that the terminal parts of both dark and light cells did not project above the surface epithelium indicate that the buds localized in the wall epithelium of circumvallate papillae in the pig are exposed to greater strain than those in the sheep in the same postnatal period (Tichy 1992b).…”
supporting
confidence: 78%
See 3 more Smart Citations